Optimisation of 5th Generation District Heating and Cooling Networks for different Flow Configurations - Anna Dell\'Isola; Louis Hermans; Lieve Helsen (Journal of Sustainable Development of Energy, Water and Environment Systems, 2025)

(untitled)
Heating and cooling sectors are pivotal in the European Union’s pursuit of climate neutrality by 2050. District heating and cooling networks, in particular the 5th generation, offer a valuable solution for reducing primary energy use and carbon dioxide emissions. This paper delves into the control optimisation of 5th generation district heating and cooling networks using white-box model predictive control techniques. The aim is to develop a nonlinear model predictive control approach for a 5th generation district heating and cooling network characterised by a directional medium flow and compare it to a non-directional medium flow network also controlled by nonlinear model predictive control. Physics-based models of building envelopes and hydraulics, developed in Modelica, are used. A model predictive control simulation is carried out to investigate the system’s operation and make a comparison of both model predictive controlled 5th generation district heating and cooling networks. Despite being less flexible, the directional configuration achieves lower energy use and good thermal comfort by leveraging fluctuating network temperatures.